EPIDEMIOLOGY OF DENGUE IN JETIS PUBLIC HEALTH CENTRE, YOGYAKARTA 2013-2016 - Azip Hasbi Asidik; Rokhmayanti Rokhmayanti; Sri Supraptiningsih; Yudha Puratmaja (Universitas Ahmad Dahlan, 2020)
Background: Dengue disease is found in tropical and sub-tropical climates worldwide, especially in urban and semi-urban areas. Of 70% of actual cases exist in Asia. The incidence of DHF in Indonesia during 2018 amounted to 24.73 per 100,000 inhabitants. Yogyakarta City is one of the dengue susceptible areas that receive serious attention from the health authorities. Jetis Public Health Centres is one of the PHC in Yogyakarta with high dengue incidence with one mortality. The purpose of this study was to describe the epidemiology of dengue cases based on time, place, people, observe dengue trend, and assess the larva free rate targetâ€™s achievement.Methods: This research was descriptive quantitative using secondary data obtained from Jetis Primary Health Centre's health information system, Yogyakarta. Dengue data year 2013-2016 was analysed using descriptive epidemiology (time, place, and people) to show the dengue trend. Last, the larva free rate was compared between targets and achievements.Results: In 2016, the dengue case increased from 81 to 104 in 2014 with one mortality. Out of 104 cases, 37 cases occurred in the Bumijo village, 33 cases in Cokrodiningratan village, 34 cases in Gowongan village. 85.58% of DHF cases occur at age â‰¥ five years, and 57.69% happen in women. The achievement of larvae free rate was 67.73% and had not reached the determined target. There was a tendency for an increase in dengue cases from May to June during the observed year.Conclusions: 2016 was the peak of dengue cases during 2013-2016. Women and people aged more-equal to five years were the most infected group. Most of the cases were found in Bumijo village. Larva's free rate in Jetis was not achieving the target. June was the peak of the case in 2016.